EXPLORING THE UNIQUENESS OF POST SCHOOL TRANSITION PROGRAM FOR STUDENTS WITH DISABILITIES IN SPECIAL EDUCATION: A STUDY ON CURRICULUM DIVERSIFICATION IN INDONESIA (Proceedings of the World Conference on Children and Youth, 2021)
Students with disabilities pursuing higher education face special challenges. The research is intended to 1) identify the kinds of academic assessment, 2) analyze the implementation of the running curriculum, 3) elicite the instructional strategies upon the readiness for college admission. This study was a survey on school policy involving 39 high schools of special education in Central Java, Indonesia. Data was collected by means of questionnaire and interview of experience-based teaching aligned to the curriculum. The questionnaire was used get the data on the curriculum content and the employed instructional strategies. In addition, the interview was to get data on the impact of instructional strategy. The data from the questionnaire were analyzed descriptive quantitatively, while the qualitative data from the interview was used to crosscheck and support the resulted analysis of quantitative data . The results showed that 1) the academic assessment washighly individualized, 2) the curriculum and instruction were diversified on the basis of students’ needs and capabilities, 3) the curriculum and instructional strategies give better impct of vocational skills rather than academic competence. The research reached the conclusion that individual and diversified curriculum and instruction impemented in special schools turn to be typical strategies in preparing the academic readiness for college admission
Keywords: Post-school-transition; diversification; disability; college